Inhibition of liver metastasis from orthotopically implanted colon cancer in nude mice by transfection of the TIMP-1 gene into KM12SM cells. - Yamauchi, K; Ogata, Y; Nagase, H; Shirouzu, K (2001)
To determine whether the tissue inhibitor of metalloproteinases 1 (TIMP-1) can modulate in vivo tumor growth and metastasis, we transfected TIMP-1 cDNA into KM12SM human colon carcinoma cells and determined the implanted tumor volume and incidence of liver metastasis in orthotopically implanted colon cancer in nude mice. We also treated the implanted tumors with repeated intraperitoneal injections of recombinant human TIMP-1 (rTIMP-1), and compared the inhibitory efficacy on liver metastasis with that achieved by the TIMP-1 transfectants. The TIMP-1 transfectants had a significantly greater inhibitory effect, in association with TIMP-1 expression, on the growth of the primary tumor and on liver metastasis as compared with the controls. However, the intraperitoneal administration of rTIMP-1 did not decrease the rate of liver metastasis. In situ hybridization demonstrated that TIMP-1 mRNA in the cecal tumors implanted with the highly produced KM12SMT-2 cells with TIMP-1 was mainly expressed by the tumor cells. These results suggest that the increased expression of TIMP-1 in KM12SM cells was responsible for their decreased metastatic potential, and that the endogenous increase in TIMP-1 production by the tumor cells might be more effective for counteracting the matrix metalloproteinases (MMPs) in tumor tissue and for inhibiting liver metastasis from colon cancer than the exogenous administration of TIMPs.